MASYARAKAT MINANGKABAU PERANTAU TANAH DATAR DI KOTA PEKANBARU ( Kasus Perantau dari Jorong Gunung Nagari Tanjung Alam Kecamatan Tanjung Baru) - Yanti, Delfa Fitri; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Jorong Gunung Nagari Tanjung Alam, Tanjung Baru Subdistrict, Tanah Datar District, is an area location in the foothills of Mount Merapi, this Perantau coming to Pekanbaru City as an push for a place that is able to provide jobs for people who want to work and the opportunities for people trading in markets in city of Pekanbaru increase income for family. The purpose this study was first, to determine the characteristics Minangkabau migrants from Jorong Gunung Nagari Tanjung Alam, Tanjung Baru Subdistrict, Tanah Datar District, Pekanbaru City. Secondly to find out the driving factors of Â Minangkabau people who came from Jorong Gunung Nagari Tanjung Alam, Tanjung Baru Subdistrict, Flat Land District, which migrated in Pekanbaru City. The type of research that I use in this case is a type of descriptive research with qualitative analysis methods. The location of this research was conducted in Pekanbar u City due to the large number of Minangkabau people originating from the natural Jorong Gunung Nagari Tanjung Tanjung Baru sub-district Tanah Datar regency to migrate to complain in the city of Pekanbaru. Data collection techniques that the author did by observation, interviews and documentation. While data analysis is done with qualitative analysis. The results of this study indicate that the Perantau of Jorong Gunung Nagari Tanjung Alam Subdistrict of Tanjung Baru Regency Flat Land that came to the city of Pekanbaru had a driving and pulling factor. The driving factors include reduced natural resources, narrowing of employment and reasons for marriage. While the pull factor is the opportunity to get a job and high salary or wages, and the pull or solicitation of people who are considered able to provide protection Â Keywords: Minangkabau Society, Merantau, Economic Change